EFFICACY OF MISOPROSTOL AND PROSTAGLANDIN E2 GEL FOR INDUCTION OF LABOR IN TERM PREGNANCY - Qazi, Qudsia; Fatima, Syeda Sitwat; Wahab, Samdana; Syed, Wajeeha (Journal of Postgraduate Medical Institute, 2020)
Objective: To compare the efficacy of Misoprostol with prostaglandin E2 in terms of induction to labor and delivery intervals in women with full term pregnancy. Methodology: This randomized controlled trial was conducted in the Department of Obstetrics and Gynecology, Lady reading Hospital (LRH), Peshawar from July 2017 to June 2018 on 116 patients who were admitted for induction of labor. All the selected patients were randomly allocated into two groups i.e. group A who received 50 mcg tablet of Misoprostol and group B who received 2 mg of Prostaglandin E2 gel vaginally. The main outcome variables were interval from induction to labor, induction to delivery and mode of delivery. Student t test was applied for calculation of difference between the two groups to find out the efficacy of Misoprostol and Prostaglandin E2 Gel in induction and onset of significant uterine contractions and induction to delivery interval. Results: The interval from insertion of drug to the onset of labor (7.26 ±4.77 hours versus 12.03 ±6.94 hours) and induction to delivery intervals (10.32 ±6.89 hours versus 15.04 ±8.16 hours) were shorter in group A than in group B. Cesarean section rate was higher in group A (24.1%) than in group B (12.1%). Conclusion: Vaginal Misoprostol was more effective than prostaglandin E2 for elective induction of labor due to shorter induction to labor and delivery intervals.